2014
DOI: 10.1155/2014/418302
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultrasound on Monitoring the Evolution of the Collagen Fiber Reinforced nHAC/CS CompositesIn Vivo

Abstract: To date, fiber reinforce scaffolds have been largely applied to repair hard and soft tissues. Meanwhile, monitoring the scaffolds for long periods in vivo is recognized as a crucial issue before its wide use. As a consequence, there is a growing need for noninvasive and convenient methods to analyze the implantation remolding process in situ and in real time. In this paper, diagnostic medical ultrasound was used to monitor the in vivo bone formation and degradation process of the novel mineralized collagen fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Chen et al. 46 also indicated that a chitosan (CS), nHA, and collagen fiber composite membrane might serve as a desired alternative for improving bone cell growth. Li et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al. 46 also indicated that a chitosan (CS), nHA, and collagen fiber composite membrane might serve as a desired alternative for improving bone cell growth. Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Jin et al 45 suggested that the efficacy of bone regeneration of collagen-HA bilayer membrane was superior to collagen-HA single-layer dense membrane on bone regeneration of SD rat cranial defects. Chen et al 46 also indicated that a chitosan (CS), nHA, and collagen fiber composite membrane might serve as a desired alternative for improving bone cell growth. Li et al 47 also suggested that HA in conjunction with a resorbable collagen membrane might be an acceptable alternative to repair the alveolar ridge deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound sonography (USG) of the rats was performed on day 9. Ultrasound images were taken at D. Y. Patil hospital and Research Centre, Kolhapur by prosound α-10 premier diagnostic ultrasound system (1.1 mechanical indexes, 80 transmission gains) equipped with a 5-10 MHz probe [31,32] for ear pinna scans. Rats were anesthetized in a prone position with an exposed examination area.…”
Section: In Vivo Study 251 Transplantation Of 3d Printed Ear Pinnamentioning
confidence: 99%
“…Mineralisation can be monitored in an animal model using ultrasound. [89] Researchers implanted mesenchymal stem cell-seeded 3D matrices into rats and were able to follow the osteogenesis, degradation, and calcification of these constructs over time. These techniques are still relatively uncommon in research practice but given that ultrasound does not rely upon ionising radiation and requires no sample preparation, it may become more ubiquitous in future.…”
Section: Ultrasoundmentioning
confidence: 99%